Development Development of Religious and Moral Values through the Subuh Bahagia Program at Nurul Falah Mosque, Keracak: Indonesia - Rudi Hartono; Taufiq, Taufiq (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2025)
The development of religious and moral values is an important aspect in fostering community life, particularly among the younger generation. One of the efforts undertaken to achieve this is through mosque-based religious activities. This study aims to describe the development of religious and moral values through the Subuh Bahagia program at Nurul Falah Mosque, Keracak, Ciwandan District, Cilegon City. The Subuh Bahagia activities include congregational dawn prayer, shared breakfast, distribution of vegetables or fruits to women, and the provision of pocket money for schoolchildren. The research employed a qualitative approach with a descriptive research design. The findings indicate that the Subuh Bahagia program is able to instill religious values, social awareness, togetherness, and empathy within the community. This program also plays a role in strengthening ukhuwah Islamiyah and fostering positive moral attitudes in a sustainable manner